2018
DOI: 10.1021/acs.orglett.8b02786
|View full text |Cite
|
Sign up to set email alerts
|

De Novo Synthesis of Phenols and Naphthols through Oxidative Cycloaromatization of Dienynes

Abstract: In this work, a rhodium-catalyzed oxidative cycloaromatization of dienynes, which provides a highly straightforward and efficient way to access polysubstituted naphthols and phenols under mild conditions, is described. Challenged electron-withdrawing groups are well tolerated in this protocol, and late-stage phenyl ring formation is demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 55 publications
0
15
0
Order By: Relevance
“…Larock et al reported a 6‐ endo ‐ dig cyclization of alkynyl benzyl ketones by treatment with excess iodine monochloride (Scheme b) . Recently, Zi group realized an efficient rhodium‐catalyzed oxidative cyclization of enynes in the construction of 2‐naphthols and phenols with remarkable substrate scope, albeit necessitating an external oxidant (Scheme c) . During our study toward intramolecular α‐arylation reactions, we found that ortho ‐bromobenzyl‐substituted α‐fluoroketones 1 under palladium catalysis resulted in the formation of 2‐naphthols 2 .…”
Section: Methodsmentioning
confidence: 67%
See 3 more Smart Citations
“…Larock et al reported a 6‐ endo ‐ dig cyclization of alkynyl benzyl ketones by treatment with excess iodine monochloride (Scheme b) . Recently, Zi group realized an efficient rhodium‐catalyzed oxidative cyclization of enynes in the construction of 2‐naphthols and phenols with remarkable substrate scope, albeit necessitating an external oxidant (Scheme c) . During our study toward intramolecular α‐arylation reactions, we found that ortho ‐bromobenzyl‐substituted α‐fluoroketones 1 under palladium catalysis resulted in the formation of 2‐naphthols 2 .…”
Section: Methodsmentioning
confidence: 67%
“…However, previously reported methods are mainly limited to accessing 1‐naphthol derivatives. To date, only a handful of examples of the de novo construction of polysubstituted 2‐naphthols have been reported . Larock et al reported a 6‐ endo ‐ dig cyclization of alkynyl benzyl ketones by treatment with excess iodine monochloride (Scheme b) .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…NaBAr4 F (10 mol%), L2 (10 mol% On the other hand, phenols and naphthols were also assembled by Rh-catalyzed oxidative cycloaromatization of dienynes using pyridine N-oxide as external oxidant (Scheme 17). 26 The proposed mechanism involves the formation of a dienyl-ketene intermediate followed by its 6e - electrocyclization/aromatization. The intermediate ketene could be trapped as the ethyl ester derivative when ethanol was used as solvent.…”
Section: Intramolecular Reactionsmentioning
confidence: 99%